Police misconduct, complaints and public regulation - Beggs, John (Oxford University Press, 2009)
The organization of policing in England and Wales, and the regulation of police forces -- The suspension and removal of chief officers by police authorities and the Secretary of State -- Complaints and misconduct I: the Independent Police Complaints Commission (IPCC) -- Complaints and misconduct II: overview of the 2004 and 2008 conduct and performance regulations, and associated appeals -- The police (performance) regulations 2008 -- Standards of professional behaviour and the initial handling of a report -- Investigations under schedule 3 of the Police Reform Act 2002 and the police (conduct) regulations 2008 -- Misconduct proceedings under the police (conduct) regulations 2008 -- The police (conduct) regulations 2004 -- Special (fast-track) cases under the police (conduct) regulations 2004 and 2008 -- Chief officer reviews, internal appeals, and the police appeals tribunals -- Abuse of process -- Probationers -- Inquests -- Police-related criminal offences